THE EFFECT OF COST OF PRODUCTION ON DETERMINING THE SELLING PRICE OF ARABIC COFFEE WITH EXTERNAL FAILURE COSTS AS MODERATING VARIABLES FROM FARMERS TO PT VOLKOPI INDONESIA IN TAKENGON (CENTRAL ACEH REGENCY) - Yulisfan, Yulisfan (Asosiasi Dosen Akuntansi Indonesia, 2020)
The main aims of this study is to analyse the effect of the cost of production on the determination of the selling price of ?asalan? arabica coffee with external failure costs as a moderating variable from farmers to the company. This type of research is causal associative research. The research method uses secondary data collection techniques. The population in this study all farmers in Takengon who sell the ?asalan? coffee to PT. Volkopi Indonesia in 2015 to 2018. The sampling method used in this study is to use the census method means that all farmers in Takengon who sell to the company. Data were processed using regression analysis with moderating variables using residual tests. The results of the multiple regression analysis used show that the effect of cost of production on the determination of the selling price of Arabica coffee origin simultaneously has a positive and significant effect on prices. But from the results of the study it can also be concluded that external failure costs are not able to significantly moderate the selling price.